Evaluasi Kinerja Organisasi Melalui Pendekatan Business Process Management - Jeni Susyanti; Muhammad Ikhsan Arief Nugraha (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Organizational performance assessment is a crucial aspect in determining the effectiveness and efficiency of business processes. The Business Process Management (BPM) approach offers a systematic framework that enables organizations to understand, manage, and optimize business processes on an ongoing basis. This research aims to evaluate organizational performance through the implementation of BPM using a case study at a public sector institution. The research method used is a descriptive qualitative study with a case study approach. The research results show that implementing BPM can improve operational efficiency, service quality and transparency of work processes. Recommendations are presented for further optimization in process measurement and management.Must be supported by continuous training, adequate information system integration, and an effective change management approach.